HAEMATOLOGICAL TOXICITIES OF GEMCITABINE PLUS CISPLATIN VERSUS FLUOROURACIL, CISPLATIN, PLUS DOCETAXEL FOLLOWED BY CONCURRENT CHEMORADIOTHERAPY IN LOCOREGIONALLY ADVANCED NASOPHARYNGEAL CARCINOMA - Rehman, Abdul; Haider, Ghulam; Ramchand , Aakash; Khan, Shumaila Nawaz; Saher , Sana; Mahmood , Raheela; Khattak, Yasir Rehman; Anaum ,; Siddiqua , Aisha; Aqeel, Muhammad Arsalan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Nasopharyngeal carcinoma is endowed with unique epidemiological characteristics, treatment modalities, and prognostic considerations. Patients with bulky primary tumours and extensive nodal involvement are categorized as locoregionally advanced NPC. These patients present a high-risk cohort in terms of the unfavourable prognostic features. In this patient cohort, the 5-year local control rates have been observed to fluctuate within the range of 69-79%. The objective was the assessment of the local control and adverse haematological toxicity profiles of neoadjuvant chemotherapy (NACT) (i.e., docetaxel, cisplatin, plus fluorouracil (TCF) and gemcitabine plus cisplatin (GC)) followed by concurrent chemoradiotherapy (CCRT) in patients with locoregionally advanced nasopharyngeal carcinoma (LANPC) was the primary objective of this work. Methods: Patients aged 16-65 years, confirmed NPC, stage III-IVA disease and ECOG performance score ‰¤2 were enrolled in this prospective study. Besides the common CCRT regimen, the patients received NACT with docetaxel 30 mg/m2, cisplatin 40 mg/m2 plus fluorouracil 750 mg/m2 (Group I) or gemcitabine 1 g/m2 plus cisplatin 80 mg/m2 (Group II). At 6 weeks after completion of CCRT, treatment response was assessed with the RECIST criteria. Adverse haematological events were evaluated with peripheral white blood cells, neutrophils, haemoglobin, and platelets after each cycle of NACT. Results: Of the total 68 enrolled patients with locoregionally advanced NPC (LANPC), 50 (73.5%) were male patients. Group I consisted of 36, while Group II comprised 32 patients. The mean (interquartile range) age of the patients in Group I was 40.9±11.6 (30.3-51.8) years, while in Group II was 38.6±11.3 (29.5-51.0) years. Complete response (CR) of the treatment was higher and partial response (PR) was lower in Group II compared to Group I (71.9% vs. 44.4% and 18.6% vs. 50%, respectively). Haematological toxicity profiles were consistent in Groups I and II, illustrating mild anaemia and lymphopenia, severe neutropenia and a mixed pattern of thrombocytopenia. Conclusion: Among patients with LANPC, GC-based NACT showed superior CR compared with TCF-based NACT. However, the haematological toxicity profiles in the two groups were comparable.